Drivers' preferences for electric cars in Italy. Evidence from a country with limited but growing electric car uptake. (July 2020) - Danielis, Romeo; Rotaris, Lucia; Giansoldati, Marco; Scorrano, Mariangela
Highlights: We estimate drivers' preferences between an electric and a petrol car in Italy. Compared with previous Italian studies, driver preferences have changed. Ceteris paribus, drivers have a positive attitude towards electric cars. Monetary incentives are the most effective measure for electric car uptake. Cheap electric cars with limited driving range are needed in the Italian market. Abstract: So far, Italy has shown a much lower electric vehicle (EV) adoption rate than other European countries. In an effort to understand the motivations for the limited but growing EV uptake, this paper focuses on Italian drivers' preferences resulting from a stated preference survey carried out in October-December 2018. This paper complements the international literature and updates previous Italian surveys administered by the authors in the past years (Valeri and Danielis, 2015; Giansoldati et al., 2018). The econometric analysis of the stated choices confirms that the vehicle attributes such as purchase price, fuel economy, and driving range play a very relevant role. The time spent to charge the vehicle affects negatively the respondents' utility, while the fast charging network density is not yet perceived as significant or carries a counter-intuitive sign. On the contrary, the possibility to park EVs for free, even for a limited time, in the city central areas is positively valued by the respondents. Comparing our estimates with previous Italian studies, in particular with Giansoldati et al. (2018) who uses a similar questionnaire but on an earlier and more limited sample, there are hints of a change in the perception of the Italian drivers towards EVs. A noticeable difference is the value of the EV alternative specific constant. Giansoldati et al. (2018) find a negative value while this study finds a positive one. A second finding is that the willingness to pay for an additional driving range kilometre is lower than that previously found, indicating that Italian drivers are becoming more confident on EV driving range. Scenario analysis indicates that in Italy financial incentives would have a larger impact on the probability of buying an EV than technological improvements.